(untitled) (The Journal of Building and Land Development, 2021)
Capacity of Local Government Authorities (LGAs) to deliver land services has been a major challenge throughout the Developing world and increasingly academic works have been aligned to address it. This paper examines LGAs land service delivery capacity and performance in 8 LGAs in Dodoma Tanzania. The LGAs were reached through in-depth interviews and observation of land administration practices in relation to the availed resources. Findings suggest that deficiency in technical and human resource are not directly related to titling performance in five of the eight LGAs an indicator that there is a limited link between resources and performance. This paper advocates for building competence on the existing pool of human resources by equipping them with the necessary skills, equipments and competence rather than hiring of new worker of almost the same calibre. Availability of adequate basic land information infrastructures could as well facilitate achieving an adequate performance in terms of land titling and related transactions. Engaging the private sector is also recommended for massive and timely delivery of land services. To the general public, education and training programs on relevant laws and policies are still needed in order to extend the level of awareness on best land administration practices. Â Key words: Tanzania; Land Administration; technology, human resource and equipment; finances